(Quality and originality in scientific research from the point of view of the participants in the course (qualification of scholars of Bayt al-Hikma) - عبد الحسين, سمية معن; ناصر, ماجد حميد (Journal of Economics and Administrative Sciences, 2020)
Research aims (Quality and originality in scientific research from the point of view of the participants in the course (qualification of scholars of Bayt al-Hikma) To find out how satisfied the participants about the training course held by the house of wisdom (research community), To develop and maximize the capacity of researchers in the field of writing scientific research, As well as establishing frameworks and concepts and standards related to quality and authenticity scientific research, The role played by this kind of research in the service of the movement of the human journey towards progress and prosperity.On this basis was the research community, their number was (23) common to the majority of them held a bachelor's degree, Has been the design of the questionnaire Included a set of paragraphs presented to members of the community, Aim to find out the extent of the benefit accruing to participants in the state, Has been reached conclusions to the effect to this state and was part of the project department of quality management and institutional development in its quest for continuous development one, Add to that the advancement of the work of the house of wisdom, Requires the rehabilitation of the necessary elements in it, and the most important researchers working in, Under it was put a set of recommendations aim to develop this type of software in the future, Of them try to allocate a special budget to support scientific research at the house of wisdom, And to the holding of advanced training courses to complement the objectives of the program become familiar with more methods and tools of scientific research.